WEBSITE SECURITY ANALYSIS CURUG VILLAGE GOVERNMENT USING OPEN WEB APPLICATION SECURITY PROJECT (OWASP) - Hilda, Syahrul Dwi; Heryana, Nono; Ridha, Azhari Ali (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Cybersecurity has become a crucial issue in the current digital era, especially for government websites that are often targeted by attacks. According to the National Cyber and Crypto Agency (BSSN), government websites are vulnerable to hacking. This study aims to analyze the security of the Curug Village Government website using the Open Web Application Security Project (OWASP). The analysis was conducted on the ten main categories of web application security vulnerabilities listed in OWASP Top 10 2021, including Broken Access Control, Cryptographic Failures, Injection, Insecure Design, Security Misconfiguration, Vulnerable and Outdated Components, Identification and Authentication Failures, Software and Data Integrity Failures, Security Logging and Monitoring Failures, and Server-side Request Forgery. The results of the testing showed that 4 out of 8 vulnerabilities fall into the OWASP TOP 10 for 2021, particularly in the categories of Injection and Security Misconfiguration. Recommendations for improvements are provided based on these findings, which are expected to help the Curug Village Government strengthen their cybersecurity.